Charge Transfer from Carbon Nanotubes to Silicon in Flexible Carbon Nanotube/Silicon Solar Cells. Issue 48 (10th November 2017) - Li, Xiaokai; Mariano, Marina; McMillon‐Brown, Lyndsey; Huang, Jing‐Shun; Sfeir, Matthew Y.; Reed, Mark A.; Jung, Yeonwoong; Taylor, André D.
Abstract: Mechanical fragility and insufficient light absorption are two major challenges for thin flexible crystalline Si‐based solar cells. Flexible hybrid single‐walled carbon nanotube (SWNT)/Si solar cells are demonstrated by applying scalable room‐temperature processes for the fabrication of solar‐cell components (e.g., preparation of SWNT thin films and SWNT/Si p–n junctions). The flexible SWNT/Si solar cells present an intrinsic efficiency ≈7.5% without any additional light‐trapping structures. By using these solar cells as model systems, the charge transport mechanisms at the SWNT/Si interface are investigated using femtosecond transient absorption. Although primary photon absorption occurs in Si, transient absorption measurements show that SWNTs also generate and inject excited charge carriers to Si. Such effects can be tuned by controlling the thickness of the SWNTs. Findings from this study could open a new pathway for designing and improving the efficiency of photocarrier generation and absorption for high‐performance ultrathin hybrid SWNT/Si solar cells. Abstract : Flexible and thin single‐walled carbon nanotube (SWNT)/Si solar cells are fabricated using scalable and room‐temperature processes. They present a high power conversion efficiency of 7.5% without any light‐trapping structure. Transient absorption spectroscopy shows a significant charge generation and injection of excited charge carriers from SWNTs to Si that can be smoothly tuned by the amount of nanotube films.